PEMBELAJARAN MENULIS TEKS DRAMA MENGGUNAKAN MODEL JIGSAW - Livia Sensialiana; Sofiah Andriani; Mimin Sahmini (IKIP Siliwangi, 2019)
This research is motivated by the difficulties of students when learning to write drama texts. Students feel less confident and don't focus on expressing their ideas or ideas. This affects low student learning outcomes. The formulation of the problem proposed in this study is whether the jigsaw learning model can improve the learning outcomes of junior high school students in writing drama texts. The purpose of this study was to determine the effectiveness of the jigsaw learning model to improve student learning outcomes in writing drama texts. The method used in this study, namely the quantitative method in the form of a pretest-posttest one group. Experiments were conducted on one class which was given a drama text writing ability test. A pretest was conducted to determine the initial ability while the posttest was conducted to determine the ability of students after being given treatment in the form of learning to write drama text using a jigsaw learning model. The results showed that the jigsaw learning model could improve student learning outcomes in writing drama texts. This is evidenced by the significant increase in the average pretest, which is 63 and the posttest average value, which is 76. Thus, it can be concluded that the effective jigsaw learning model is used to improve the learning outcomes of junior high school students in writing drama texts.